Veste e abbigliamento nella Ciropedia: presenze e ambivalenze - SANTINI, Carlo (Euphrosyne, 2003)
Abstract As Levine Gera points, we find in the Cyropedia several tales in which a robe is involved; the dress of the characters is always mentioned in the relevant passages of the work and the Median stole becomes for Cyrus a pattern of his career from the very beginning to the attainment of highest power and of the kingdom. The analysis focuses this motif symbol of the kingship and examines step by step its impress on the narrative framework.